EMOTIONAL AND MORAL IMMATURITY AND PERSONALITY DISORDERS - Strus, Włodzimierz (Studia Psychologica: Theoria et praxis, 2004)
The article goes out from impeachment of thesis, that the cognitive developmental approach explains the human's moral kelter in a sufficient way. The author proves that emotional maturity is the condition of correct morality, and simultaneously is determined by proper moral development. The categories of disorders, wich have undergone analysis, particularly clearly illustrate these dependences: dissocial personality disorder (psychopathology) and obsessive compulsive personality disorder. In view of both types of disorders the emotional as well as moral immaturity assume the extreme intensification. In conclusion it was also admitted, that correct emotional development as well as moral are indispensable for a mature personality, being simultaneously the symptoms of psychical health. The serious disturbances in these spheres are fundamentally the factors of psychopathology.